ASESMEN ONLINE PADA PENDIDIKAN ANAK USIA DINI: STUDI DI RA HAYATUDDINIYAH - Helmah, Noorsyifa; Irayana, Ika (Titik Fokus Karya, 2023)
The COVID-19 pandemic, which affected the global education sector, forced educational institutions to transition from face-to-face to online learning. RA Hayatuddiniyah, an early childhood education institution in Hulu Sungai Utara, successfully implemented online assessments during the pandemic. This research aimed to analyze the online assessment format used at RA Hayatuddiniyah, focusing on the methods and factors that supported its implementation. The study employed a qualitative case study approach, with the participants including the school principal, teachers, and parents of the students. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data presentation, and conclusion techniques, with validity ensured through triangulation. The findings revealed that the online assessment at RA Hayatuddiniyah employed three main assessment methods: structured and unstructured conversations, students' work, and portfolio assessments. Supporting factors for successful online assessment included permission and support from the school principal, teachers’ ability to adapt to technological advancements, and adequate parental support. This study provides valuable insights into the challenges and success factors in online assessments in early childhood education and offers recommendations for improving future implementation.